Penegakan Hukum Terhadap Pelanggaran Hak Cipta yang Dilakukan oleh Penyanyi (Cover) di Media Sosial (Youtube) yang Mendapat Bayaran Kepada Pencipta Lagu Ditinjau dari Undang-Undang Hak Cipta - I Putu Yudha Wira Krisna; Heryanto Amalo; Rudepel Petrus Leo (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The purpose of this research is to understand the substance of the regulation of copyrighted works in Indonesia, especially those related to cover versions and to find out more about the protection and legal remedies for copyright holders of copyrighted works regarding cover versions of songs that are sung again for commercial purposes based on Law Number 28 of 2014 concerning Rights. Create. This type of research is empirical juridical. There are seven factors that cause copyright infringement, namely economic, cultural, technological, law enforcement, education, unemployment and environmental factors. In Article 54 and Article 55 of Law Number 28 of 2014 concerning Copyright. If the violator has been proven to have committed a copyright violation, they can be subject to civil sanctions, namely for anyone who violates copyright regulations, that person can be subject to compensation where the lawsuit can be reported to the Commercial Court and subject to sanctions. Eradicating copyright infringement requires an in-depth understanding of the causes and violations that need to be handled seriously. That intellectual property in copyright protection for musical works on digital platforms should pay attention to statutory regulations regarding copyright protection in Indonesia, namely Law Number 28 of 2014 concerning Copyright.